Optimizing Patient Outcomes in Multidisciplinary Dental Care: Insights from Restorative, Orthodontic, Endodontic, and Oral Surgery Perspectives - Dr.mohammed Ahmed Alghamdi; Dr.Suliman A Alnujaidi; Dr.abdulaziz Abdulrahman Almujil; Dr.Mohammad A Alrowias; Dr.Sulaiman Abdullah Alhowaish; Dr.Abdullah Saleh Alshehri; Dr.Naifmohammed Alotaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Systemized care in dental specialties involves collaboration between restorative, orthodontic, endodontic, and oral surgeon specialties to improve patient outcomes and oral health, highlighting the importance of collaboration in modern dentistry. Aim of work: To explore the multidisciplinaryrole of restorative orthodontic, endodontic, and oral surgery in optimizing patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Optimizing, Patient, Outcomes, Multidisciplinary, Dental Care, Restorative, Orthodontic, Endodontic, and Oral Surgery.The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Multidisciplinary dental care is becoming the gold standard in dentistry, driven by the collective goal of optimizing patient outcomes. By uniting the strengths of restorative, orthodontic, endodontic, and oral surgery perspectives, dental professionals can offer patients comprehensive, effective treatment plans. This collaborative approach not only enhances the quality of care but also enables patients to enjoy functional, aesthetically pleasing, and healthy smiles for years to come.